Relationship between Perceived Organizational Justice and Performance Appraisal Satisfaction: Insights of Employees - Shrestha, Prakash; Bhujel, Sanu Babu; Bhandari, Sita (Journal of Business and Social Sciences, 2024)
This study examines the relationship between perceived organizational justice dimensions and performance appraisal satisfaction. This study adopts a quantitative research design. Data was collected from 250 structured questions that were distributed to employees of five financial institutions. Only 61.20 percent of them were found to be useful. The findings indicate that employees are more likely to be satisfied with their performance appraisal if they believe that rewards or results are distributed fairly. The findings show a significant relationship between overall satisfaction with performance appraisal and organizational justice in the results. Furthermore, overall satisfaction with the performance appraisal process has a positive relationship with the perceived organizational justice of the techniques used. Finally, the findings imply that employees who believe they receive equitable interpersonal treatment throughout the performance review process are also likely to be highly satisfied with their appraisal. Thus, the effectiveness of the appraisal system is also influenced by how unbiased it is perceived to be. For employees to accept the entire process and its results without question, the distributive, procedural, and interactional justice components should have a positive effect on them.